2014
DOI: 10.1016/j.ejps.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Tribo-electric charging and adhesion of cellulose ethers and their mixtures with flurbiprofen

Abstract: The pervasiveness of tribo-electric charge during pharmaceutical processing can lead to the exacerbation of a range of problems including segregation, content heterogeneity and particle surface adhesion. The excipients, hydroxypropyl methylcellulose (HPMC) and methylcellulose (MC), are often used in drug delivery systems and so it is important to understand the impact of associated factors on their charging and adhesion mechanisms, however, little work has been reported in this area. Such phenomena become more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…The electrostatic forces generated in such cases are a concern since the accumulated charge on these particles can cause segregation, adhesion or agglomeration leading to multiple manufacturing complications [15][16][17] . Electrostatic forces may also result in undesirable adhesion of charged drug particles to drug devices such as inhalers and can affect both the trajectory and the deposition of aerosols within the lungs 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The electrostatic forces generated in such cases are a concern since the accumulated charge on these particles can cause segregation, adhesion or agglomeration leading to multiple manufacturing complications [15][16][17] . Electrostatic forces may also result in undesirable adhesion of charged drug particles to drug devices such as inhalers and can affect both the trajectory and the deposition of aerosols within the lungs 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Triboelectrification has been used to study the impact of the counter ion on flurbiprofen salts as a consideration during the preformulation process [22], reduce the charging of flurbiprofen (a drug with a high propensity for charging) in binary mixtures of cellulose ethers [23], ordered mixing [24] and recently as a way of manipulating the charge of their final product of solid dispersions using single solvents and binary mixtures of solvents [25].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…However, hydrophilic derivatives of cellulose ethers, more specifically methylcellulose (MC) and hydroxypropyl methylcellulose (HPMC), are considered to be the main excipients of choice in the development of compressed hydrophilic matrix tablets [13,14]. Recently, tribo-electric charging behaviour of Methocel ® A4M, F4M, E4M, K4M, K15M and K100M, in plain and binary mixtures with the negatively charging API, flurbiprofen, have been studied [15]. The magnitude of the positive charge of the polymers, was distinct from the majority of other excipients previously reported, and was generally higher [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, tribo-electric charging behaviour of Methocel ® A4M, F4M, E4M, K4M, K15M and K100M, in plain and binary mixtures with the negatively charging API, flurbiprofen, have been studied [15]. The magnitude of the positive charge of the polymers, was distinct from the majority of other excipients previously reported, and was generally higher [9,15]. Furthermore, it was reported that when highly charged flurbiprofen came into contact with Methocel ® , irrespective of its grade, it attached to its surface due to opposite polarities and the tribo-electric charge of the final powder mixture was significantly dissipated [15].…”
Section: Introductionmentioning
confidence: 99%